Agenda of Higher Education gets accomplished through Service-Learning: Lady Doak College experiences - Pushpalatha, A. Mercy (Silliman Journal, 2022)
Indian Higher Education has had an emphasis on inclusion of service in curriculum right from the 1960s. The National Service Scheme (NSS) launched in 1969 had one of its objectives as ‘Utilizing the knowledge in finding practical solutions to individual and community problems’. Lady Doak College founded in the year 1948 by the passionate service of Ms. Katie Wilcox, a Christian Missionary from the USA, has left a legacy where Higher Education, when interwoven with service, gears up students to become socially committed women leaders. The evaluative and non-evaluative service programs then offered became service-learning (SL) in some departments after 2003. From 2005, SL had been institutionalized when it became an integral part of the curriculum for extra credits. Hence, all 13 departments started offering SL programmes/courses as part of their curriculum. These departmental SL Programmes paved way for interdisciplinary community-based research, addressing some of the ethical concerns experienced when Service-Learning was practiced as pedagogy. Since 2013, the restructured curriculum offered at undergraduate level had the mandatory component of ‘Life Frontier Engagement’ (LFE). The LFE has offered an academic experience enabling the student to create new knowledge as solution to a community based problem resulting in whole person development and consequently, the agenda of Higher Education is accomplished. This experience of Lady Doak College in evolving Service-Learning as pedagogy and subsequently the emergence of Life Frontier Engagement to address the ethical issues experienced in SL is presented in this paper.